Analisis Beban Kerja Teknisi Pesawat Pada Maintenance Phase 1 King Air B200 di Balai Besar Kalibrasi Fasilitas Penerbangan - Maulana, Firdaus Abizar; Riyanti, Lilies Esthi; Kurniawan, Iwan Engkus (Politeknik Penerbangan Indonesia Curug, 2024)
In aircraft maintenance, it is necessary to calculate the workload, to find out how much manpower is needed for a job. Determining manpower requirements to ensure maintenance work is carried out in an efficient manner and at a high level of quality. The Aviation Facilities Calibration Center (BBKFP) still applies a conventional approach in carrying out maintenance, with crowds without a clear manpower estimate for the work carried out by technicians. The method for calculating workload on Maintenace Phase 1 King Air B200 series is the Full Time Equivalent (FTE) method. The purpose of this research is to find out the amount of workload in Maintenance Phase 1 of the KingAir B200 series, to find out the suitability of the optimal number of manpower in Maintenance Phase 1 of the King Air B200 Series, and to find out the number of technicians that corresponds to the workload from the FTE calculations in Maintenance Phase 1 of the King Air B200 Series. The results of this research showed that 63.63% of the sections were still in the Overload condition, 9.09% were in the Underload category and 27.27% were in the Fit / Normal Category.